2016
DOI: 10.1039/c6cc02848a
|View full text |Cite
|
Sign up to set email alerts
|

Rod-shaped and fluorine-substituted hydroxyapatite free of molecular immunopotentiators stimulates anti-cancer immunity in vivo

Abstract: Herein, rod-shaped and fluorine-substituted hydroxyapatite nanoparticles (FHA) were synthesized using a facile hydrothermal method. The rod-shaped FHA significantly increased the cellular uptake of a model antigen by bone marrow dentritic cells in vitro, improved antigen presentation in vivo, stimulated immune-related cytokine secretion in vitro and ex vivo, and enhanced the anti-cancer immunity in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…It is well known that rod-shaped nano-HAP crystals grow in a calcium phosphate solution containing a small amount of fluoride 14, 15 . The challenge is to construct a nanorod array of oriented HAP on a substrate.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that rod-shaped nano-HAP crystals grow in a calcium phosphate solution containing a small amount of fluoride 14, 15 . The challenge is to construct a nanorod array of oriented HAP on a substrate.…”
Section: Introductionmentioning
confidence: 99%
“…In previous reports, research demonstrated that the antitumor effect of HA NPs might be related to the intrinsic physicochemical characteristics, including crystal size, morphology, and surface functionality. Many studies also attempted to change the structure of HA NPs in order to improve the inferior proliferation inhibition effect on tumor cells, but the improvement was very limited. Due to the initial preferential orientation of the HA crystal, , it was easier to obtain needle-like or rod-like HA nanocrystals with imbalanced aspect ratios in the process of growth. The undiversified structure exerted poor adjustability as well as showed imperfect performance. Certainly, a few reports are also available on spherical HA NPs; however, the as-obtained structures are reported to have diameters up to several hundreds of nanometers with irregular assembled morphologies, which cannot be defined as authentic sphere-like nanostructure.…”
mentioning
confidence: 99%
“…For example, Cui and co‐workers [ 100 ] used carnosine modified graphene oxides as the adjuvant and carrier to deliver the antigen OVA to induce a strong OVA‐specific antibody response and recruit CD4+ T and CD8+ T cells. And, Tsuji and co‐workers [ 101 ] synthesized the fluorine‐substituted hydroxyapatite (FHA) nanoparticles, which are generated by F − instead of OH − in hydroxyapatite as both carrier and immune adjuvants for conveying OVA antigen to APCs ( Figure A). In this system, the uptake rate of FHA‐OVA by DCs was significantly enhanced.…”
Section: Intelligent Strategies Based On the Cells In The Immune Cycle For Improving Cancer Immunotherapymentioning
confidence: 99%
“…Reproduced with permission. [ 101 ] Copyright 2016, The Royal Society of Chemistry. B) Schematic diagram of bacterial membrane coated nanoparticle (BNP), which could adsorb the tumor antigens released in the process of radiotherapy to form a personalized vaccine.…”
Section: Intelligent Strategies Based On the Cells In The Immune Cycle For Improving Cancer Immunotherapymentioning
confidence: 99%